The Change and Continuity in the Morphology of Traditional Malay Kampung in Medan, Indonesia 1913-2024 - Sri Elfina Panjaitan; Salmina Wati Ginting; Dwi Lindarto Hadinugroho (Ikatan Peneliti Lingkungan Binaan Indonesia, 2025)
This study examines the morphological transformation of the traditional Malay kampung in Medan, Indonesia, from the colonial period (1913) to the present day (2024). Using a typo-morphological approach, the research analyzes spatial changes of streets, buildings, and open spaces, revealing how historical, social, and economic dynamics have shaped the kampung’s evolution. The findings indicate that early settlements were structured around the Malay Sultanate called Istana Puri in Kota Matsum III district. This area showed a clear spatial arrangement of Malay traditional settlement. However, post-independence urbanization, migration, and economic shifts led to increasing density, irregular patterns, and the fading of traditional Malay architectural identity. By 2024, commercial activities dominated major roads, while residential areas moved inward, resulting in fragmented spatial patterns. The study highlights the impact of colonial legacies, the 1946 social revolution, and economic growth in shaping Medan’s urban transformation. Understanding these changes provides insights for urban planning strategies that balance modernization with cultural preservation. This research contributes to the discourse on historical urban morphology and the challenges of maintaining cultural identity in evolving cityscapes.